Performance evaluation of AODV using blackhole attack in MANET / Muhammad Idham Padil - Padil, Muhammad Idham (2022)
MANET are self-contained, multi-hop, wireless, transitory networks that operate under throughput, power, and energy constraints. Mobile wireless networks are more prone to attacks than fixed wireless networks. These networks are vulnerable to security due to unprotected and open wireless broadcast channels and inadequate physical security. Blackhole attacks are active attacks in which the attacking node continuously declares that it has the quickest route to any desired network node, although it does not. Consequently, all packets will travel through it, enabling the blackhole node to forward or delete packets during data transfer. As most studies examine reactive, proactive, or hybrid routing protocols, such as AODV and DSDV or AODV and ZRP, there is also a lack of study comparing AODV with different nodes and simulation time. This research simulates and compares the performance of the AODV routing protocol with and without a blackhole attack. Moreover, the throughput, packet delivery ratio, and end-to-end delay of AODV and AODV with blackhole are compared to evaluate their respective performance. Using Network Simulator 2 (NS2), two scenarios with varying numbers of nodes beginning at 10, 20, 30, 40, and 50 are simulated for a total of 60 seconds. With a lower throughput of 60.82 Kbps, a poorer packet delivery ratio of 16.27%, and a more significant end-to-end delay of 1531.36 milliseconds, the results show that AODV with blackhole attack performs worse than without blackhole attack for all performance criteria. This project also could be enhanced for future work by examining or suggesting other network and transport layer security techniques used to prevent these attacks.